Pengembangan Lembar Kerja Peserta Didik Berbasis Hots Pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Kelas VII SMPN 3 Palopo - Puput Kamaruddin; Nurdin K; Dodi Ilham (Indonesian Journal of Islamic Educational Review, 2025)
This study focuses on the development of student worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) for Islamic Religious Education and Character Development subjects at SMPN 3 Palopo. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), this research aims to create learning materials that enhance students' critical thinking skills. Initial observations revealed that conventional teaching methods and materials were failing to engage students effectively, resulting in decreased learning motivation. The developed HOTS-based worksheets were validated by subject matter experts, media specialists, and language experts, achieving an average validation score of 90%, indicating high validity. During implementation with eighth-grade students, the worksheets demonstrated a practicality score of 87%. Academic performance improved significantly, with average test scores increasing from 65.3 on pre-tests to 85.7 on post-tests, representing a 31.3% improvement. Student feedback was overwhelmingly positive, with 93% reporting that the worksheets enhanced their understanding of the material, particularly when working on analysis and evaluation-based problems. The integration of religious values with critical thinking skills allowed students to not only understand religious concepts but also analyze their application in daily life. Despite these promising results, the study acknowledges limitations, including the restricted sample size from a single school and the relatively short research duration, which limits observation of long-term impacts. This research contributes significantly to the development of HOTS-based teaching materials in Islamic Religious Education and provides a model that can be adapted for other subjects to support higher-quality educational outcomes aligned with the Merdeka Curriculum's competency-based learning approach.